KEPASTIAN HUKUM PERPANJANGAN HAK GUNA BANGUNAN RUMAH SUSUN DIATAS TANAH HAK PENGELOLAAN - Ivan Fasyah (2021)
Article 17 of the Law on Flats states that the construction of flats can originate from Building Use Rights (HGB) above Management Rights (HPL). Construction of flats or apartments that are carried out on HPL can potentially cause problems in the future. Problems that may occur when the owner of the apartment unit together with the developer will extend the HGB above the HPL. In the matter of the extension of the right, how is the legal certainty of extension of the HGB on the HPL as well as regarding the responsibility of the developer to the apartment unit owner if the extension of the HGB is rejected by the Land Office. This study uses a normative juridical method, which examines a problem using library materials or secondary data in the form of regulations and literature related to the problem. The results of the study illustrate that it is necessary to make derivative laws and regulations legal certainty regarding the extension of HGB above HPL and responsibility for developers if they cannot extend the HGB above HPL. The government as the holder of power in the land and agrarian sector should make derivative regulations that regulate this matter in order to achieve legal certainty.The government as the holder of power of the land and agrarian sector should make derivative regulations governing legal certainty regarding the extension of HGB over HPL and responsibility for developers if they cannot extend the HGB above HPL.